A gender-sensitive ethical reading of Old Testament texts : the role of African women as characters in the text and exponents of the text - Nkabala, Nambalirwa Helen (Old Testament essays, 2013)
The essay examines the contribution of African women towards a gender-sensitive ethical reading of the OT texts at two levels. First, the story of Moses' African wife who is rejected by her in-laws in Num 12, draws a picture of an African woman as a character in the text. Secondly, the essay proceeds to highlight the Talitha Cum hermeneutic, which entails various contributions such as: inculturation, post-colonialism, the hermeneutic of life and the bosadi hermeneutic from some African women, both academic and grass roots, as exponents of the text. It is further argued in the essay that Talitha Cum, is an excellent example of African women's gender-sensitive ethical readings of biblical texts because it helps to assert the position of women and more specifically African women wherever they are. It is also observed that the Talitha Cum hermeneutics lays the foundation for a life-centered ethic that serves to promote the dignity of women and the entire humanity. Consequently, I present an example of Talitha Cum in action. It is the case of Angelina Atyam, an African woman from northern Uganda who refuses to look on after the abduction of her daughter but instead forms a self-support group for her and other affected parents. The essay concludes that with the presence of Talitha Cum, African women are in a position to re-awaken their strength.